SICKLE CELL ANAEMIA AND MALARIA - Lucio Luzzatto (Mediterranean Journal of Hematology and Infectious Diseases)
Sickle cell anaemia is a major chapter within haemolytic anaemias; at the same time, its epidemiology is a remarkable signature of the past and present world distribution of Plasmodium falciparum malaria. In this brief review, in keeping with the theme of this journal, we focus on the close and complex relationship betweeen this blood disease and this infectious disease. On one hand, heterozygotes for the sickle gene (AS) are relatively protected against the danger of dying of malaria, as now firmly established through a number of clinical field studies from different parts of Africa. In addition, experimental work is consistent with a plausibile mechanism: namely, that in AS heterozygotes P falciparum-infected red cells sickle preferentially and are then removed by macrophages. On the other hand, patients who are homozygous for the sickle gene and therefore suffer from sickle cell anaemia (SCA) are highly susceptible to the lethal effects of malaria. The simplest explanation of this fact is that malaria makes the anaemia of SCA more severe; in addition, in SCA there is often hyposplenism, which reduces clearance of parasites. From the point of view of public health it is important that in malaria-endemic countries patients with SCA, and particularly children, be protected from malaria by appropriate prophylaxis.